Saudi Arabia : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Saudi Arabia is recovering strongly from the pandemic-induced recession. Higher oil prices provide an opportunity for accelerating further the strong reform drive brought about under Vision 2030.